A likely association between low mannan-binding lectin level and brain fog onset in long COVID patients - Bulla, Roberta; Rossi, Lucrezia; Furlanis, Giovanni; Agostinis, Chiara; Toffoli, Miriam; Balduit, Andrea; Mangogna, Alessandro; Liccari, Marco; Morosini, Giorgia; Kishore, Uday; Manganotti, Paolo (Frontiers in Immunology, 2023)
Brain fog can be described as a constellation of new-onset neuropsychiatric sequelae in the post-acute phase of COVID-19 (long COVID). The symptoms include inattention, short-term memory loss, and reduced mental acuity, which may undermine cognition, concentration, and sleep. This cognitive impairment, persisting for weeks or months after the acute phase of SARS-CoV-2 infection, can significantly impact on daily activities and the quality of life. An important role for the complement system in the pathogenesis of COVID-19 has emerged since the beginning of the pandemic outbreak. A number of pathophysiological characteristics including microangiopathy and myocarditis have been attributed to dysregulated complement activation due to SARS-CoV-2 infection. Mannan-binding lectin (MBL), the first recognition subcomponent of the complement lectin pathway, has been shown to bind to glycosylated SARS-CoV-2 spike protein, genetic variants of MBL2 are suggested to have an association with severe COVID-19 manifestations requiring hospitalization. In the present study, we evaluated MBL activity (lectin pathway activation) and levels in the sera of a cohort of COVID-19 patients, presenting brain fog or only hyposmia/hypogeusia as persistent symptoms, and compared them with healthy volunteers. We found significantly lower levels of MBL and lectin pathway activity in the sera of patients experiencing brain fog as compared to recovered COVID-19 patients without brain fog. Our data indicated that long COVID-associated brain fog can be listed among the variegate manifestations of increased susceptibility to infections and diseases contributed by MBL deficiency.